Differential Oxygenation in Tumor Microenvironment Modulates Macrophage and Cancer Cell Crosstalk: Novel Experimental Setting and Proof of Concept - Campillo, Noelia; Falcones, Bryan; Otero, Jordi; Colina, Roser; Gozal, David; Navajas, Daniel; Farré, Ramon; Almendros, Isaac (Frontiers in Oncology, 2019)
Hypoxia is a common characteristic of many solid tumors that has been associated with tumor aggressiveness. Limited diffusion of oxygen generates a gradient of oxygen availability from the blood vessel to the interstitial space and may underlie the recruitment of macrophages fostering cancer progression. However, the available data based on the recruitment of circulating cells to the tumor microenvironment has been so far carried out by conventional co-culture systems which ignore the hypoxic gradient between the vessel to the tumor interstitium. Here, we have designed a novel easy-to-build cell culture device that enables evaluation of cellular cross-talk and cell migration while they are being simultaneously exposed to different oxygenation environments. As a proof-of-concept of the potential role of differential oxygenation among interacting cells we have evaluated the activation and recruitment of macrophages in response to hypoxic melanoma, breast and kidney cancer cells. We found that hypoxic melanoma and breast cancer cells co-cultured with normoxic macrophages enhanced their directional migration. By contrast, hypoxic kidney cells were not able to increase their recruitment. We also identified well described hypoxia-induced pathways which could contribute in the immune cell recruitment (VEGFA and PTGS2 genes). Moreover, melanoma and breast cancer increased their proliferation. However, oxygenation levels affected neither kidney cancer cell proliferation nor gene expression, which in turn resulted in no significant changes in macrophage migration and polarization. Therefore, the cell culture device presented here provides an excellent opportunity for researchers to reproduce the in vivo hypoxic gradients in solid tumors and to study their role in recruiting circulating cells to the tumor in specific types of cancer.